Pemodelan Pola Arus di Perairan Pesisir Banyuasin, Sumatera Selatan - Surbakti, Heron; Purba, Mulia; Nurjaya, I Wayan (Maspari Journal : Marine Science Research, 2011)
A two-dimensional model to investigate the pattern of current in estuary of Banyuasin has been developed. The properties of tide, wind, and current were measured to understand the dynamics of estuarine environment. Based on the information, the model of current simulation were performed. The simulation of model shows that offshore flow during flood tide and inland flow during ebb tide. Maximum current speed was recorded during mean-sea-level towards high tide of 0.8716 m s-1, while the minimum was 0.0661 m s-1 observed during ebb tide. The difference current speed between model and recorded is 0.04 m s-1. Keywords : Modeling, Current, Tidal, Banyuasin. ABSTRAK Model dua dimensi dibangun untuk melihat pola arus di perairan pesisir Banyuasin. Karakteristik pasang surut, angin dan arus diukur untuk memahami dinamika lingkungan estuari. Berdasarkan karakteristik parameter tersebut, model dan simulasi pola arus dibangun. Berdasarkan hasil simulasi diperoleh gambaran bahwa pola arus menuju laut saat periode pasang dan menuju daratan saat periode surut. Kecepatan arus maksimum diperoleh saat mean sea level menuju pasang tertinggi dengan kecepatan 0.8716 m s-1, dan kecepatan arus minimum diperoleh saat kondisi surut terendah sebesar 0.0661 m s-1. Perbedaan kecepatan arus hasil model dengan hasil pengukuran adalah sebesar 0.04 m s-1. Kata Kunci : Pemodelan, Arus, Pasang Surut, Banyuasin